2023
DOI: 10.1101/2023.01.28.525750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The parasubthalamic nucleus refeeding ensemble delays feeding initiation

Abstract: The parasubthalamic nucleus (PSTN) is responsive to refeeding after food deprivation and PSTN subpopulations can suppress feeding. However, no study directly addressed the role of PSTN neurons activated upon food access resumption. Here we show that the ensemble of refeeding-activated PSTN neurons massively increases the latency to initiate refeeding with both familiar and novel food but exerts limited control over the amount of food consumed by hungry mice. This ensemble also delays sucrose consumption but ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
3
0
0
Order By: Relevance
“…It becomes activated upon sudden food ingestion, exposure to aversive stimuli that reduce feeding (e.g., visceral malaise, novelty, predator odor), and administration of anorectic hormones, thus encoding states of satiety and food rejection. The functional manipulation of PSTN glutamatergic neurons as a whole or subsets of PSTN neurons (e.g., those expressing Tac1 or Adcyap1) demonstrated that their activation serves to suppress food or sucrose intake (40,43,44,(48)(49)(50)(51). Consistent with prior literature, chemogenetic activation of PSTN Tac1 neurons virtually ablated the consumption of alcohol and saccharin in our experimental conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It becomes activated upon sudden food ingestion, exposure to aversive stimuli that reduce feeding (e.g., visceral malaise, novelty, predator odor), and administration of anorectic hormones, thus encoding states of satiety and food rejection. The functional manipulation of PSTN glutamatergic neurons as a whole or subsets of PSTN neurons (e.g., those expressing Tac1 or Adcyap1) demonstrated that their activation serves to suppress food or sucrose intake (40,43,44,(48)(49)(50)(51). Consistent with prior literature, chemogenetic activation of PSTN Tac1 neurons virtually ablated the consumption of alcohol and saccharin in our experimental conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, while it is possible that the small subset of PSTN neurons co-expressing Crh and Tac1 promotes alcohol intake via NK1 signaling, the activity of PSTN Tac1 neurons as a whole inhibits alcohol drinking. This inhibitory influence of PSTN Tac1 neurons extends to saccharin drinking and is consistent with the general pattern of feeding/drinking suppression previously reported for this population (40,43,44).…”
Section: Chemogenetic Stimulation Of Pstn Tac1 Neurons Reduces the Co...supporting
confidence: 90%
See 1 more Smart Citation